2021
DOI: 10.1155/2021/5220226
|View full text |Cite
|
Sign up to set email alerts
|

Release of HMGB1 in Podocytes Exacerbates Lipopolysaccharide-Induced Acute Kidney Injury

Abstract: Objective. Acute kidney injury (AKI) usually occurs during sepsis. Inflammation factors, such as high-mobility group box 1 (HMGB1), are dramatically upregulated under septic conditions. In our current work, the functions of HMGB1 in AKI were explored. Methods. An AKI model was induced by the lipopolysaccharide (LPS) challenge in C57 mice. Podocytes were challenged by LPS for different durations. Subsequently, podocytes transfected with HMGB1 siRNA were exposed to LPS for 24 h. The expressions of supernatant HM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 25 publications
0
10
0
Order By: Relevance
“… [72] It has been demonstrated that LPS damages podocytes, which constitute the glomerular filtration barrier. [ 73 , 74 ] Knockdown of HMGB1 attenuates the endotoxin-induced injury in cultured podocytes. [73] Furthermore, tubular epithelial cells express mitochondrial dysfunction after HMGB1 exposure.…”
Section: Hmgb1 In the Development Of Sepsis-induced Organ Failuresmentioning
confidence: 99%
See 2 more Smart Citations
“… [72] It has been demonstrated that LPS damages podocytes, which constitute the glomerular filtration barrier. [ 73 , 74 ] Knockdown of HMGB1 attenuates the endotoxin-induced injury in cultured podocytes. [73] Furthermore, tubular epithelial cells express mitochondrial dysfunction after HMGB1 exposure.…”
Section: Hmgb1 In the Development Of Sepsis-induced Organ Failuresmentioning
confidence: 99%
“…[ 73 , 74 ] Knockdown of HMGB1 attenuates the endotoxin-induced injury in cultured podocytes. [73] Furthermore, tubular epithelial cells express mitochondrial dysfunction after HMGB1 exposure. [73] Another study reports that HMGB1 accumulates in renal tissue during Gram-negative sepsis and enters the urine, and the interaction between HMGB1 and TLR4 turns tubular epithelial cells into inflammatory promoters.…”
Section: Hmgb1 In the Development Of Sepsis-induced Organ Failuresmentioning
confidence: 99%
See 1 more Smart Citation
“…Infection accompanied by the release of HMGB1 contributes to circulatory dysfunction and is one of the major contributing factors of AKI. Experimental studies have shown that HMGB1 release from podocytes is induced by lipopolysaccharide (LPS), which subsequently exacerbates AKI (Gao et al, 2021). The release of HMGB1 worsened circulatory dysfunction.…”
Section: Introductionmentioning
confidence: 99%
“…In ischemic AKI, the aseptic inflammatory response associated with damage-associated molecular patterns (DAMPs) is considered one of the first pathological processes ( Hepokoski et al, 2021 ; Liu et al, 2021 ). Renal tubular cell necrosis releases intracellular molecules such as high mobility group box 1 (HMGB1), histones, heat kinin, and fibronectin into the extracellular space and activates recognition receptors on either tissue-resident cells or recruited leukocytes via the DAMPs ( Wang et al, 2020c ; Gao et al, 2021 ). Cell necrosis then leads to a massive secretion of pro-inflammatory cytokines and chemokines, further aggravating the inflammatory cascade response.…”
Section: Introductionmentioning
confidence: 99%